Correlation between the NMR Chemical Shifts and Thiolate Protonation Constants of Cysteamine, Homocysteine, and Penicillamine - Ferreira de Santana, Juliana; Mirzahosseini, Arash; Noszál, Béla (Journal of Spectroscopy, 2022)
1H and 13C NMR measurements were carried out to explore anticipated correlations between chemical shifts versus thiolate basicities and redox potentials of cysteamine, homocysteine, penicillamine, and their homodisulfides. All correlations were analyzed and statistically evaluated. The closest correlation was observed for the αCH nuclei concerning 1H and 13C NMR data. Since neither site-specific basicities nor site-specific redox potentials can be directly measured by any means in peptides and proteins containing several thiol and/or disulfide units, these data provide a simple method and predictive power to estimate the aforementioned site-specific physicochemical parameters for analogous sulfur-containing moieties in related biopolymers.